ANALISIS SENTIMEN ULASAN APLIKASI GAME HAY DAY MENGGUNAKAN ALGORITMA RANDOM FOREST - Effendi, Puput Amelia; Tati Ernawati (Universitas Lampung, 2025)
This study aims to analyze the sentiment of Hay Day game user reviews on the Google Play Store platform using the Random Forest (RF) algorithm. The data utilized consisted of 5,060 reviews, which were processed through pre-processing stages, including text cleaning, tokenizing, stopword removal, and stemming. TF-IDF was employed as a feature extraction technique to determine word importance within the reviews. The analysis results indicate that the majority of user sentiment tends toward negative (1,821 comments), suggesting dissatisfaction with technical aspects of the game, such as bugs, pay-to-win systems, and account access issues. The RF model evaluation demonstrates an accuracy of 80.41%, with precision values of 79.3%, recall of 80.41%, and F1-score of 78.55%. This research recommends that game developers prioritize improvements to frequently complained technical issues and enhance communication with users to increase player satisfaction and loyalty.